Karakteristik Sifat Fisik Tanah Wilayah Hulu Daerah Aliran Sungai (DAS) Rejoso Kabupaten Pasuruan - Putri, Peggy Rahmawati; Purwadi, Purwadi; Priyadarshini, Rossyda (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2023)
Watershed Characteristics (DAS) are a specific description of watersheds characterized by topography, soil type, geology, vegetation, and land use. Physical characteristics can be the primary reference in planning, implementing, and evaluating appropriate watershed management. The research was carried out from January to August 2022 in the upstream Rejoso watershed (DAS) area, consisting of Tosari and Puspo Subdistricts, Pasuruan Regency, East Java. This study aims to obtain information about physical characteristics in the upstream region of the Rejoso watershed. This study uses a survey method of five land uses in this region. Five land uses namely, potato horticultural gardens with an altitude of 1,850-2,500 masl, horticultural gardens (potato, leek, and cabbage) of 1,350-1,850 masl, and forest land use of 800-1,350 masl are found in this area. Three sampling points were determined for each land use. The results showed that the physical characteristics of the soil in the upstream Rejoso watershed varied greatly with the slope. At the study site was classified as very steep, with soil density from low to medium, soil texture dominated by sand and dust fractions with dusty clay texture class, and permeability classified as slow to medium, moderate, and low to high organic matter content.Keywords: Soil physics, upstream watershed Rejoso